Wide Awake Local Anesthesia No Tourniquet (WALANT) Versus Bier’s Block, in Internal Fixation of Unstable Metacarpal and Phalangeal Fractures of the Hand: A Comparative Study - Kastanis, Grigorios E; A, Pantouvaki; P, Kapsetakis; I, Stavrakakis; MK, Siligardou; P, Bitados; E, Georgali; C, Andriopoulos; M, Manolaraki (International Journal of Innovative Research in Medical Science, 2023)
Hand fractures are a common injury in emergency department, and the majority of these are stable injuries that can be treated conservatively with excellent functional results. When respective injuries are characterized as unstable, surgical reduction and stabilization is necessary. Generally, these operations are conducted under regional or general anesthesia to avoid pain and tourniquet for bloodless surgical fields. Wide Awake local anesthesia no tourniquet (WALANT) procedure is described as a local injection of anesthetic agent and epinephrine without tourniquet application, with scope to allow local anesthesia without other sedation and at the same time hemostasis. The purpose of the study is to compare the functional assessment of the hand function during a period of three months after surgical intervention for unstable metacarpal and phalangeal fractures under WALANT versus Biers block. Material &Methods: Between May 2021 to October 2022, 43 patients with unstable metacarpal and phalangeal fractures underwent open reduction and internal fixation, 21 cases with Biers block(BB) anesthesia and rest with WALANT technique. Metacarpal fractures appeared in 29 cases and phalangeal fractures in 14 patients. Patients were operated within the first week from the injury. According to implants they employed locking plates, screws and Kirschner wires in two groups. Results: At three months postoperatively, Quick Dash Score is better in WALANT group while patients’ satisfaction does not differ between two groups. In WALANT group immediate postoperative median VA Score appeared 2/10, while in the Biers block group appeared 6/10. Patients which underwent WALANT technique were discharged on the same day after operation, while the patients with regional anesthesia the next postoperative day. Mean duration of analgesic use was sorter in WALANT group (2,3 days) than in BB group (5,7 days). Conclusion: Οbjective of surgical treatment of unstable hand fractures (metacarpal-phalangeal) is early mobilization and enhance hand functionality to avoid stiffness and tendon adhesions. Wide Awake local anesthesia no tourniquet technique is an alternative sedative procedure which immediately offers postoperative numerous advantages (low-cost technique, no complication from tourniquet, decrease sensation of intra or postoperative pain) compared with Bier’s block anesthesia. Based on our results we believe that WALANT technique offers many benefits in surgical treatment of hand fractures and is suggested as first choice anesthesiologist procedure.